Consumo e qualidade do café da manhã de pré-escolares - Guimarães, Ana Carolina Vieira de Teixeira (2014)
Under-five children pass through a vulnerable phase, inappropriate eating habits may negatively affect their growth. The absence of breakfast is one of these habits. The aims of this study were to assess prevalence and quality of breakfast as well as factors associated with its absence by preschool children. This is a sociodemographic, house-hold survey, cross-sectional study with probability sampling involving 463 children at ages of two to five years old both male and female. The assessment concerned the habit of having breakfast and the food consumed. The food consumption was assessed through food frequency questionnaire. The children who consumed breakfast and the children who did not have this habit were compared regarding daily energy intake, macronutrients, some types of micronutrients and fiber by means of t he Mann-Whitney test. The following variables were also investigated: age, sex, maternal age, maternal education level, economy class, preschool nurseries, maternal occupation, use of feeding bottles, time spent in front of the television, nutritional status, lunch replaced with snacks, dinner replaced with snacks and number of daily meals. The Pearson Qui-squared test was used in the bivariate analysis and multiple logistic regression was used to assess the association between the variables studied and the omission of breakfast. The absence of breakfast was observed in 9.3% of the samples. The average energy intake for breakfast was of 286,3 ±135,6 kcal, representing 18% of the diet total energy. 51.7% of the preschool children presented proper energy intake at breakfast. The most common foods in the diet of children were milk and dairy products (89.7%), simple sugars (61.1%) and bread group (42.1%). Factors such as lunch replaced with snacks (OR: 2,54; p=0,037) ,less than five daily meals (OR: 1,98; p=0,018) and the absence of breakfast all presented association. The average intake for all nutrients analyzed were higher in children who had breakfast with meaningful difference for zinc (p=0.027) and iron (0.043) consumption. Despite children’s diet of better quality is associated with the habit of having breakfast, the absence of the meal has been shown to be high. There should be greater encouragement towards the daily consumption of breakfast as well as the increased intake of health food, whole grains, dairy products and healthy fats.